PHONETIC CHARACTERISTICS OF ENGLISH PRONUNCIATION DELIVERED BY JOKO WIDODO AT THE APEC CEO SUMMIT 2014: AN ACOUSTIC PHONETIC STUDY ON SUPRASEGMENTAL FEATURES - Lily Gusti Yossa; Jufrizal Jufrizal (Universitas Negeri Padang, 2019)
Every speaker is always influenced by home language knowledge in pronunciation activity. Because of that, this research interested to describes Phonetic characteristics of English pronunciation delivered by Joko Widodo through Suprasegmental features such as Pitch, loudness, and Pause and analyzed by PRAAT software. The source of data is speech script from video at the APEC CEO Summit 2014. In the data analysis, there are 10 Pitch, 17 loudness and 9 pause forms. From 10 pitch forms, the use of tone contours often appeared is fall-rise tone. The rest is fall and level tone. The lowest frequency is 80.23 Hz and the highest frequency reaches 190.9 Hz. From 17 loudness forms, there are 11 data that the speaker placed a primary stress differently. Then, there are 6 data that placed primary and secondary stress inappropriately, if these were compared with the oxford dictionary. Moreover, the decibel range of the speaker tended to use around 70 decibel and above which is categorized to normal decibel. In the 9 pause forms, there are eight inter lexical pauses which means the pauses happened among lexical. Thus, by suprasegmental features mean to reveal the phonetic characteristics had by Joko Widodo as a foreign speaker.